Complementing sequence-derived features with structural information extracted from fragment libraries for protein structure prediction - Liu, Siyuan; Xu, Qijiang; Wang, Tong; Shao, Bin; Yin, Jian; Liu, Tie-Yan (BMC Bioinformatics, 2021)
Fragment libraries play a key role in fragment-assembly based protein structure prediction, where protein fragments are assembled to form a complete three-dimensional structure. Rich and accurate structural information embedded in fragment libraries has not been systematically extracted and used beyond fragment assembly. To better leverage the valuable structural information for protein structure prediction, we extracted seven types of structural information from fragment libraries. We broadened the usage of such structural information by transforming fragment libraries into protein-specific potentials for gradient-descent based protein folding and encoding fragment libraries as structural features for protein property prediction. Fragment libraires improved the accuracy of protein folding and outperformed state-of-the-art algorithms with respect to predicted properties, such as torsion angles and inter-residue distances. Our work implies that the rich structural information extracted from fragment libraries can complement sequence-derived features to help protein structure prediction.